ADOPSI SISTEM E-COMMERCE SEBAGAI MODEL LAYANAN PENGUNJUNG DESA WISATA DI KABUPATEN BONDOWOSO - Mastika, I Ketut; -, Sasongko; Pramono, Rudy Eka; Julianto, Didik Eka; Wahyuni, Sri (Jurnal Master Pariwisata (JUMPA); Volume 05, Nomor 02, Januari 2019DO - 10.24843/JUMPA.2018.v05.i02.p05, 2019)
This paper examines the adoption of e-commerce system models in the rural tourism sector. Rural tourism business infrastructure barriers be resolved with application ride sharing system named ' Ter a ter’ and e-payment with the name ‘ E-bajer ’. Research using qualitative methods to explore information from the subject of the research. The existence of a model system for Ride Sharing such Go-jek in 50 cities in Indonesia, able to inspire the TERATER initiator, community, adopt e-commerce system as a model of service to visitors. The utilization of e-commerce helps a lot and makes it easy for rural home industry to market and Transaction. In the E-Commerce systems can guarantee the existence of real data and real money. The results of the research can be used to initiate the expansion of the adoption of e-commerce systems in the development of regional tourism its main tourist village. Keywords: E-Commerce, Tourism Village, Gojek